2020
DOI: 10.3390/jcm9123922
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Mesenchymal Stem Cells in Ulcerative Colitis: A Review on Achievements and Challenges

Abstract: The worldwide epidemiology of inflammatory bowel disease (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC), still shows an increasing trend in Asia and Iran. Despite an improvement in the treatment landscape focused on symptomatic control, long-term colectomies have not decreased over the last 10-year period. Thus, novel therapies are urgently needed in clinics to supplement the existing treatments. Mesenchymal stem cells (MSCs) are multipotent adult stem cells with immunosuppressive effects, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 90 publications
0
30
0
Order By: Relevance
“…Based on their satisfactory immunomodulatory effect, MSCs have been studied as a promising candidate for treating some inflammatory and immunologic diseases, such as graftversus-host disease (GvHD), inflammatory bowel disease (IBD), systemic lupus erythematosus (SLE), and ARDS (18)(19)(20)(21). As has been clarified, MSCs control both innate and adaptive immune response behavior through release of trophic factors, which are mediated by cell-contact-dependent and -independent mechanisms through the direct cell-cell interaction (22).…”
Section: Discussionmentioning
confidence: 99%
“…Based on their satisfactory immunomodulatory effect, MSCs have been studied as a promising candidate for treating some inflammatory and immunologic diseases, such as graftversus-host disease (GvHD), inflammatory bowel disease (IBD), systemic lupus erythematosus (SLE), and ARDS (18)(19)(20)(21). As has been clarified, MSCs control both innate and adaptive immune response behavior through release of trophic factors, which are mediated by cell-contact-dependent and -independent mechanisms through the direct cell-cell interaction (22).…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) have the potential to differentiate into cell types that can repair damaged mucosa, via inhibition of inflammatory factors and downregulation of inflammatory response [ 79 ]. A systematic review and meta-analysis confirmed the effectiveness and safety of MSCs in the treatment of UC [ 80 ], indicating that targeted MSCs hold promise for future application [ 81 ]. In a rat experiment induced by TNBS/ethanol enema, intragastric TXYF was administered once a day for 28 days.…”
Section: Pathophysiological Studiesmentioning
confidence: 99%
“…In otorhinolaryngology, biocompatible scaffolds have been used to establish a normal structure and function in an injured tissue [12]. Cell transplantation or cell therapy is the other branch utilized in regenerative medicine to modulate immune response and regenerate new tissues, via paracrine signaling, by use of various types of stem cells, including embryonic stem cells (ESCs), induced pluripotent stem cells (iPSCs), and mesenchymal stem cells (MSCs) [4]. In cell-based therapies, replacement of the lost or damaged tissues happens via engraftment of viable transplanted cells and stimulation of endogenous self-healing pathways by trophic factors [13,14].…”
Section: Regenerative Medicine and Cell Transplantation Conceptmentioning
confidence: 99%
“…Non-invasive procedures, such as computed tomography (CT) scan or magnetic resonance imaging (MRI), cannot provide enough resolution to determine most pathologies of the inner ear [53]. Therefore, transplantation of exogenous MSCs can take advantage of an array of stem cells from various tissue sources [4].…”
Section: Inner Ear and Hearing Lossmentioning
confidence: 99%
See 1 more Smart Citation